1980
DOI: 10.1111/j.1476-5381.1980.tb10860.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ACTIVITY OF RO363, A β1‐ADRENOCEPTOR SELECTIVE AGONIST

Abstract: 1 The #-adrenoceptor stimulant effects of R0363 and (-)-isoprenaline have been compared in a variety of isolated tissue preparations. 2 R0363 is approximately half as potent as (-)-isoprenaline in tissues where actions are due to #l,-receptor activation (guinea-pig atrial and ileal preparations and ventricular strips from the rabbit, rat and guinea-pig).3 In uterine and lung strip preparations from the guinea-pig, where responses are due to f32-receptor stimulation, R0363 is 100 to 350 times less active than (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…However, xamoterol has low intrinsic activity at the ß 1 -adrenoceptor [13], and might be more properly considered a selective ß 1 -adrenoceptor antagonist with a high degree of intrinsic activity. Ro 363, another phenoxypropanolamine, shows higher intrinsic activity at the ß 1 -adrenoceptor [see 14] and a high degree of ß 1 -versus ß 2 -adrenoceptor selectivity [15][16][17]. Potency of BRL 25805 in rat atrium appears comparable to that reported for Ro 363 in other ß 1 -adrenoceptor assays [14].…”
Section: Discussionsupporting
confidence: 54%
“…However, xamoterol has low intrinsic activity at the ß 1 -adrenoceptor [13], and might be more properly considered a selective ß 1 -adrenoceptor antagonist with a high degree of intrinsic activity. Ro 363, another phenoxypropanolamine, shows higher intrinsic activity at the ß 1 -adrenoceptor [see 14] and a high degree of ß 1 -versus ß 2 -adrenoceptor selectivity [15][16][17]. Potency of BRL 25805 in rat atrium appears comparable to that reported for Ro 363 in other ß 1 -adrenoceptor assays [14].…”
Section: Discussionsupporting
confidence: 54%
“…In smooth muscle preparations, xamoterol produced clear 0-adrenoceptor-mediated effects in otor sites in the two tissues. The slope only K+-stimulated uterine preparations from progesnt curve was not different from unity terone pretreated rats, a tissue in which P2-adrenocep- 1984), P2-adrenoceptors (oestrogen-pretreated guineapig uterus, rat vas deferens, oestrogen-pretreated rat uterus; Krstew et al, 1982;Kenakin, 1982) or mixed piand P2-adrenoceptor populations (guinea-pig trachea; Iakovidis et al, 1980;O'Donnell & Wanstall, e present experiments indicate that 1981) subserve inhibitory responses, adrenoceptorcit P-adrenoceptor-mediated cardiac mediated actions of xamoterol were absent. However, )oth muscle relaxant effects in some, xamoterol elicited non-l-adrenoceptor-mediated ind tissue preparations in which it was hibitory actions in guinea-pig ileal and tracheal ironotropic effects were obtained in preparations.…”
Section: Antagonistic Actions At P-adrenomentioning
confidence: 91%
“…Inotropic activity was monitored in electrically driven cat (2 Hz) and guinea-pig (4 Hz) left atrial and guineapig right ventricular strips (1 Hz). Driving stimuli were delivered to the tissues from a Grass S6 stimulator via a platinum punctate electrode using square wave pulses of2.5 ms duration at twice the threshold voltage required to drive the preparations (for further details see Iakovidis et al, 1980).…”
Section: Cardiac Preparationsmentioning
confidence: 99%
“…One may argue that we have used isoprenaline which is an agonist of both pI-and P2-adrenoceptors and, in consequence, the ,-adrenoceptor might also be related to PDE type IV. It has however been clearly shown that the stimulation of ,I-adrenoceptors in the airways is without functional effect either in man (Lofdahl & Svedmyr, 1982;1984) or in guinea-pig (Iakovidis et al, 1980;Johansson & Waldeck, 1981 who showed that rolipram or the PDE III/PDE IV inhibitor Org 30029 potentiated the inhibitory effect of fenoterol on the antigen-induced contraction of the passively sensitized human bronchial isolated smooth muscle, whereas the PDE III selective inhibitor milrinone was inactive. Zaagsma et al (1992) also demonstrated that the P-adrenergic inhibition of antigen-induced histamine release from guineapig peripheral lung was potentiated in the presence of rolipram.…”
Section: Discussionmentioning
confidence: 99%